2016
DOI: 10.17509/ijost.v1i2.3806
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation Behavior of T91 Steel in Dry and Humid Condition

Abstract: High temperature oxidation behavior of T91 ferritic/martensitic steel was examined over the temperature range of 500 to 700°C in dry and humid environments. The weight gain result revealed that oxidation occurs at all range of temperatures and its rate is accelerated by increasing the temperature. The weight gain of the oxidized steel at 700°C in steam condition was six times bigger than the dry oxidation.. SEM/EDX of the cross-sectional image showed that under dry condition, a protective and steady growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was reported that bulk Fe3O4 had the Fe-O absorption band at 570 cm -1 . Herein, this band was shifted toward a higher wavenumber since the localized electrons were rearranged on the SNP surface along with an enhanced surface bond force constant (Leong et al, 2016).…”
Section: Experimental Setup and Characterizationmentioning
confidence: 99%
“…It was reported that bulk Fe3O4 had the Fe-O absorption band at 570 cm -1 . Herein, this band was shifted toward a higher wavenumber since the localized electrons were rearranged on the SNP surface along with an enhanced surface bond force constant (Leong et al, 2016).…”
Section: Experimental Setup and Characterizationmentioning
confidence: 99%
“…Those models basically are focused on CO2 environments (Asmara & Ismail, 2011a Because concepts and methods to predict corrosion rate are calculated in different ways, it is frequently found that there are differences of the corrosion data calculated by different models under nearly identical conditions. Some models provide over-estimate of corrosion rates than others (Leong, et al, 2016). Corrosion models are formulated using various scenarios among theories and experiments (Alia, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%